Selected papers on geotechnical engineering - Vaughan, P. R. (Thomas Telford, 2009)
A collection of 20 papers by Professor Peter Rolfe Vaughan published in conjunction with a memorial symposium at the Royal Geographical Society on March 18, 2008. Includes Vaughan's obituary, full listing of his bibliography, and personal reflections from colleagues.